The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s00268-013-2146-y
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ and Long‐term Outcomes After Laparoscopic Versus Open Emergency Resection for Colon Cancer: An Observational Propensity Score‐matched Study

Abstract: Our data suggest that selective emergency laparoscopy for colon cancer is not inferior to open surgery with regard to short- and long-term outcomes. Laparoscopy resulted in a shorter length of hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 62 publications
1
20
1
Order By: Relevance
“…Patients who underwent LAP stayed in the hospital after surgery for a shorter duration of time than did those who underwent OP. Several studies have reported similar results regarding short‐term outcomes …”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Patients who underwent LAP stayed in the hospital after surgery for a shorter duration of time than did those who underwent OP. Several studies have reported similar results regarding short‐term outcomes …”
Section: Discussionsupporting
confidence: 57%
“…Several studies have reported similar results regarding short-term outcomes. [10][11][12][13] Regarding long-term outcomes in the present study, there was no significant difference in DFS or OS between LAP and OP. Some RCTs and propensity score-matched studies have shown similar results, that there was no difference in DFS or OS between LAP and OP.…”
Section: Discussioncontrasting
confidence: 45%
“…The bibliographic search identified 389 potentially relevant studies, and subsequent title and abstract screening eliminated 371 studies that obviously did not fit our inclusion criteria. Out of the remaining 18 studies, 11 studies [4,[8][9][10][11][12][13][14][15][16][17] were finally included in our meta-analysis after a full-text review ( Fig. 1).…”
Section: Results Of Study Search and Quality Assessmentmentioning
confidence: 99%
“…Meanwhile, the incidence of reoperation was comparable between ELC and EOC (fixed effects model; OR 0.95; 95 % CI 0.44, 2.04; P = 0.89). Nine studies [4,8,[10][11][12][13][15][16][17] reported postoperative mortality. Pooled data of these studies revealed that the incidence of postoperative death was comparable between ELC and EOC (fixed effects model; OR 0.54; 95 % CI 0.23, 1.28; P = 0.16).…”
Section: Outcomes Of Morbidity and Mortalitymentioning
confidence: 99%
See 1 more Smart Citation